Dancing from policy to pedagogy in China: Transgressions, surveillance and resistance from students, teachers and institutional leaders. Issue 8 (November 2020) - Rowe, Nicholas; Xiong, Xi; Tuomeiciren, Heyang
This article investigates the challenges that tertiary educators face when seeking to implement education-policy reforms in China. Our qualitative study presents the narratives of tertiary dance educators from eight universities who have actively sought to shift their pedagogical practices as acts of transgression. Their stories reveal the ways that teachers experience pressure to perpetuate authoritarian teaching practices, from their students, from other teachers, and from their institutional leaders. Viewing this learning culture through a Foucauldian lens, we critically question how an authoritarian discourse pervades the tertiary dance education system. Through this, we identify how surveillance and a continual sense of comparison (between students, teachers and institutions), sustains authoritarian pedagogies and inhibits individual teachers' approaches to educational reform.